Growth enhancement and gene expression of Arabidopsis thaliana irradiated with active oxygen species. (28th June 2016) - Watanabe, Satoshi; Ono, Reoto; Hayashi, Nobuya; Shiratani, Masaharu; Tashiro, Kosuke; Kuhara, Satoru; Inoue, Asami; Yasuda, Kaori; Hagiwara, Hiroko
Abstract: The characteristics of plant growth enhancement effect and the mechanism of the enhancement induced by plasma irradiation are investigated using various active species in plasma. Active oxygen species in oxygen plasma are effective for growth enhancement of plants. DNA microarray analysis of Arabidopsis thaliana indicates that the genes coding proteins that counter oxidative stresses by eliminating active oxygen species are expressed at significantly high levels. The size of plant cells increases owing to oxygen plasma irradiation. The increases in gene expression levels and cell size suggest that the increase in the expression level of the expansin protein is essential for plant growth enhancement phenomena.